Selecting Various Industrial Competitors Affect The Risk Level of Viet Nam Insurance Industry - Huy, Dinh Tran Ngoc (Journal of Research in Marketing (ISSN: 2292-9355), 2013)
Under a one factor model, this paperwork estimates the impacts of the size of firms’ competitors in the insurance industry on the market risk level, measured by equity and asset beta, of 7 listed companies in this category. This study identified that the risk dispersion level in this sample study could be minimized in case the competitor size doubles (measured by equity beta var of 0,107). Beside, the empirical research findings show us that asset beta min value increases from 0,037 to 0,104 when the size of competitor doubles. Last but not least, most of beta values are acceptable except a few exceptional cases. Ultimately, this paper illustrates calculated results that might give proper recommendations to relevant governments and institutions in re-evaluating their policies during and after the financial crisis 2007-2011.